Air Power in the New Counterinsurgency Era The Strategic Importance of USAF Advisory and Assistance Missions - Vick, Alan J. (RAND Corporation, 2006)
United States has engaged in counterinsurgency around the globe for more than a century. But insurgencies have rarely been defeated by outside powers. Rather, the afflicted nation itself must win the war politically and militarily, and the best way to help is to offer advice, training, and equipment. Air power, and the U.S. Air Force, can play an important role in such efforts, which suggests making them an institutional priority.